PENGARUH CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN MIFI SMARTFREN ANDROMAX DI SURABAYA - FADJAR, MUAMMAL (Jurnal Ilmu Manajemen (JIM), 2016)
The need for information and entertainment is high to make access to the Internet network in Indonesia. With the discovery of the network 4G / LTE makes access and download speeds also high. PT. Smartfren see the opportunity to bring a high-quality modem and wireless technology that is able to connect to the internet at high speed and can be used by multiple users. The company with the largest 4G network in Indonesia (Open Signal) and have a high product quality also in making the product. The purpose of this study was to determine the effect of brand image and perception of the quality of the purchasing decision. The number of respondents was 220 and questionnaires carried out in the Plaza Marina and WTC Surabaya. Methods of data collection in this study is the observation, documentation, and questionnaires. The sampling technique used was purposive sampling. Data analysis technique used is multiple linear regression analysis. The results showed that the brand image and quality perception of positive and significant impact on purchasing decisions MiFi smartfren Andromax in Surabaya simultaneously. And partially shows that the brand image and quality perception of positive and significant impact on purchasing decisions MiFi smartfren Andromax in Surabaya. Keywords: brand image, perceived quality, purchasing decision